Neurological examination: what do psychiatrists need to know?. (September 2021) - Larner, Andrew J.; Welch, Killian A.; Carson, Alan J.
SUMMARY: Psychiatrists may be daunted by the prospect of undertaking a neurological examination. In this article we briefly review the neurological signs that may be seen in the context of some common neurological disorders of cognition and movement which may present with neurobehavioural symptoms and therefore may be seen initially by psychiatrists. This approach emphasises that neurological examination is not simply an operationalised procedure but an interpretative process. We propose a minimum neurological examination suitable for use by psychiatrists. Many of the signs included are relatively simple to observe or elicit, require no special equipment, and the examination techniques involved are easy to master.